2014
DOI: 10.2105/ajph.2014.301914
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Adolescent Hopelessness and Self-Worth With Pregnancy Attempts and Pregnancy Desire

Abstract: The negative association of self-worth and the positive association of hopelessness with pregnancy attempts among young men as well as young women and the association of hopelessness with pregnancy desire among young women raise questions about why pregnancy is apparently valued by youths who rate their social and cognitive competence as low and who live in an environment with few options for material success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Children were viewed as a blessing and a source of happiness even though the economic reality of another child would constitute a substantial burden. Recent research among adolescent populations has suggested that attitudes towards pregnancy are strongly linked to the view of motherhood as one’s main source of personal satisfaction or achievement (Fedorowicz et al, 2014), a concept that may also be applicable here.…”
Section: Discussionmentioning
confidence: 99%
“…Children were viewed as a blessing and a source of happiness even though the economic reality of another child would constitute a substantial burden. Recent research among adolescent populations has suggested that attitudes towards pregnancy are strongly linked to the view of motherhood as one’s main source of personal satisfaction or achievement (Fedorowicz et al, 2014), a concept that may also be applicable here.…”
Section: Discussionmentioning
confidence: 99%
“…5 Young people who feel hopeless about their future are more likely to engage in behaviors that put them at risk of HIV, STDs, and pregnancy. 31,32 Suicide risk, measured here by increasing levels of suicide ideation and action, not only places the life of the adolescent at risk but is also a marker for experience of trauma and mental health issues. 33 • The percentage of high school students who felt sad or hopeless almost every day for two weeks or more in the past year.…”
Section: Mental Health and Suicidementioning
confidence: 99%
“…Hopelessness is a transdiagnostic psychological construct that emerges in adolescence and is characterized by rigid and persistently negative expectations about the future and helplessness to change future outcomes (Abramson et al 1989; Beck et al 1974). Hopelessness is associated with psychopathology and high–risk behaviors (Beck et al 1974), including more severe depressive symptoms (Becker-Weidman et al 2009), first onset of a major depressive episode (Mac Giollabhui et al 2017), suicidal ideation (Ayub 2009; Beck et al 1990; Daniel and Goldston 2012; Horwitz et al 2017; Kwok et al 2010), substance use (Bolland 2003), risky sexual behavior (Fedorowicz et al 2014), and increased likelihood to engage in violence (Drummond et al 2011; Stoddard, Henly, et al 2011). Despite its implication in multiple forms of psychopathology, there are limited data characterizing trajectories of hopelessness in community samples of adolescents.…”
Section: Introductionmentioning
confidence: 99%